Activation of a Cryptic Splice Site of GFAP in a Patient With Adult-Onset Alexander Disease. (December 2021) - Amano, Eiichiro; Yoshida, Tomokatsu; Mizuta, Ikuko; Oyama, Jun; Sakashita, Shingo; Ueyama, Syunsuke; Machida, Akira; Yokota, Takanori
Abstract : Background and Objective: Alexander disease (ALXDRD) is an autosomal dominant neurologic disorder caused by mutations in the glial fibrillary acidic protein ( GFAP ) gene and is pathologically defined by Rosenthal fiber accumulation. Most mutations are exonic missense mutations, and splice site mutations are rare. We report a very-late-onset autopsied case of adult-onset ALXDRD with a novel splice site mutation. Methods: Genetic testing of GFAP was performed by Sanger sequencing. Using autopsied brain tissues, GFAP transcript analysis was performed. Results: The patient presented mild upper motor neuron symptoms in contrast to the severe atrophy of spinal cord and medulla oblongata. The patient had c.619-1G>A mutation, which is located in the canonical splice acceptor site of intron 3. The brain RNA analysis identified the r.619_621del (p.Glu207del) mutation, which is explained by the activation of the cryptic splice acceptor site in the second and third nucleotides from the 5′ end of the exon 4. Discussion: GFAP gene expression analysis is necessary to clarify the effects of intronic mutations on splicing, even if they are in canonical splice sites. This case showed a much milder phenotype than those in previous cases with missense mutations at Glu207, thereby expanding the clinical spectrum of ALXDRD with Glu207 mutation.